Influence of facility caseload on subsequent survival of men with localized prostate cancer undergoing radical prostatectomy - Barzi, Afsaneh (Cancer, 2019)
BACKGROUND: Several studies have investigated the relationship between experience measured in caseload and oncological outcomes, economics, and access to care for prostate cancer care. Oncological outcomes were limited to biochemical failure after radical prostatectomy (RP). Questions remain regarding the more definitive measures of outcome and their relationship to caseload. METHODS: National Cancer Database was used to investigate the outcomes of RP in the United States. Using overall survival (OS) as the primary outcome, the relationship between facility annual caseload (FAC) for all prostate cancer encounters and facility annual surgical caseload (FASC) for those requiring RP were examined using Cox proportional hazards model. Four volume groups (VG) were defined as VG1: <50(th), VG2: 50(th)-74(th), VG3: 75(th)-89(th) and VG4: top 10 percentile of caseload. Using FAC/FASC, 11/8, 17/18, 25/26, and 47/49 percent of patients were treated at VG 1 through 4, respectively. RESULTS: Between 2004 and 2014, 488,389 patients underwent RP. At a median follow-up of 60.75 months, the median OS was not reached. There was a significant OS benefit as caseload increased. For FAC, the adjusted OS difference between VG1 and VG4 at 90(th) percentile survivorship reached 13.2 months, HR 1.30 (95% CI: 1.23–1.36, p<0.0001). For FASC this was 11.3 months, HR 1.26 (95% CI: 1.192–1.321, p<0.0001). CONCLUSION: There is a statistically significant OS advantage to performing RP at a facility with a high annual caseload. Caseload measured in all prostate cancer encounters is a better predictor of favorable outcome compared to the number of surgeries performed at a facility.